Adherence and Satisfaction of Deferasiroxversus Deferoxamine in Transfusion-Dependent Beta-Thalassemia - Mustafa Al-Khyate1 , Zeina A.Althanoon2 , Nasih A.Alkazaz3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: The present study was aimed to compare the adherence and satisfaction with deferoxamine(Desferal®) versus deferasirox (Exjade®), a novel oral iron chelator, in patients with transfusion-dependentbeta-thalassemia.Patients and Methods: In this cross?sectional, single-center study, 108 homozygous ?thalassemia majorpatients aged between 3-21 years old were enrolled. They were on regular blood transfusions and ironchelators (either deferoxamine or deferasirox) for about three months. Another fifty-six apparently healthynon-thalassemic subjects were enrolled as a control group. Results: Adherence and satisfaction wereassessedbyusing a simplequestionnaire establishedduring an interviewwithpatientsortheirparents.The serumferritinlevel was measuredbythe ELISAmethod.Our findings showed that adherence and satisfaction in the deferasirox group were more than that withdeferoxamine group patients. Serum ferritin level in the deferasirox group was significantly lower than inthe deferoxamine group at (p?0.001). while the control group was significantly lower than both patientsgroups at (p?0.001). Patients on deferasirox had lower adverse effects than the deferoxamine group sincedeferoxamine produce irritation and pain at the injection site for the patients.Conclusion: Our findings concluded that deferasirox is an effective iron chelator as deferoxamine but withbetter adherence and satisfaction than deferoxamine. Deferasirox can be used as a preferred iron chelatortherapy in iron-overload patients with beta-thalassemia.